Effectiveness of corn husk fibre on the compressive strength and water absorption of concrete containing cockle shells as coarse aggregate replacement materials - S. M., Shamsuddin; M. H., Wan Ibrahim; Yaka Aria, M. Sugiyo; Putra Jaya, Ramadhansyah; Nindyawati, Nindyawati; B. Sri, Umniati (IOP Science, 2025)
This study aimed to investigate the effectiveness of corn husk fibre (CHF) on concrete containing blood cockle shells (BCS) as coarse aggregate replacement materials in terms of compressive strength and water absorption. A total of 84 samples of concrete C30 with water-to cement ratio of 0.54 were prepared with curing period of 7, 14 and 28 days. Firstly, blood cockle shells (BCS) were utilised at 10%, 20% and 30% for coarse aggregate replacement by weight labelled as CS1, CS2 and CS3 respectively. CS1 has the highest compressive strength of 31.6 MPa, followed by CS3 and CS4. While CS3 has the highest water absorption at 3.55% in comparison to the control sample. Next, CHF were added to the concrete mixture containing the optimum content of BCS i.e. 10% (CS1) at 1%, 1.5% and 2% by volume labelled as CSH1, CSH2 and CHS3. Overall, there is significant reduction in the compressive strength where CSH2 exhibit the highest strength at 20.26 MPa. CSH3 has the highest water absorption at 3.07% in comparison to the control and CS1 sample.